A Comparative Analysis of the Representation of Disney’s White and Non-White Women in Brave (2012) and Moana (2016) - Aulia Khairunnisa (Universitas Pendidikan Indonesia (UPI), 2018)
In the earlier films produced by Disney, the female main characters are dominated by white-skinned women. Disney’s films that have non-white female main characters just emerged at the end of the 20th century. However, the question whether white women and non-white women maintain the same qualities are still going on. Thus, this study investigates the representation of Disney’s white and non-white women in Brave (2012) and Moana (2016) produced by Walt Disney Studios in the 21st century. Adopting a qualitative method, this present study analyzes the female main characters’ characterizations which are drawn upon Boggs and Petrie’s (2008) framework of characterization in films. The study also employs Corrigan’s (2010) framework of mise-en-scene to strengthen the analysis. The findings reveal that Disney’s white and non-white women are represented differently. Disney’s white women tend to be represented as a rebellious female main character in the domestic sphere. On the other hand, Disney’s non-white women represent a devoted female main character in the realm of the public sphere. Despite the differences, both female main characters represent a new archetype of Disney’s princess who is more egalitarian, brave and not dependent on men. Keywords: women representation, white and non-white, domestic and public sphere